Development of the PAI Curriculum at the Darut Tauhid III Salafi Islamic Boarding School: Wustha Study in Jungkat Village, Mempawah Regency - Al Muzali, Syaiful; Abdullah, Abdullah (Ngaji: Jurnal Pendidikan Islam, 2025)
Abstract. This study examined the development of the Islamic Religious Education (PAI) curriculum at Darut Tauhid III Salafi Islamic Boarding School, especially the Wustha Program in Jungkat Village, Mempawah Regency. The curriculum was developed through a needs analysis approach involving teachers, students, and the community to ensure relevance while preserving the pesantren’s identity. It retained the study of the yellow book and integrated interactive methods and contextual socio-religious materials. The findings showed that the curriculum improved students’ understanding and daily application of knowledge. Teachers adopted more discussion-based and problem-solving approaches, and students demonstrated higher learning motivation. Implementation faced challenges, including limited technology and teacher adaptation, as well as some resistance to change. Overall, the curriculum was accepted by the community and represented a strategic step in preparing students with strong religious competence and broader contemporary insight.   Abstrak. Penelitian ini menelaah pengembangan kurikulum Pendidikan Agama Islam (PAI) di Pondok Pesantren Salafi Darut Tauhid III, khususnya Program Wustha di Desa Jungkat, Kabupaten Mempawah. Kurikulum tersebut dikembangkan melalui pendekatan analisis kebutuhan yang melibatkan guru, santri, dan masyarakat untuk memastikan relevansi sekaligus menjaga identitas pesantren. Kurikulum ini mempertahankan kajian kitab kuning serta mengintegrasikan metode pembelajaran interaktif dan materi sosio-keagamaan yang kontekstual. Temuan penelitian menunjukkan bahwa kurikulum tersebut meningkatkan pemahaman santri dan penerapan pengetahuan dalam kehidupan sehari-hari. Guru menerapkan pendekatan yang lebih berbasis diskusi dan pemecahan masalah, dan santri menunjukkan motivasi belajar yang lebih tinggi. Pelaksanaan menghadapi tantangan, termasuk keterbatasan teknologi, adaptasi guru, serta sebagian resistensi terhadap perubahan. Secara umum, kurikulum ini diterima oleh masyarakat dan menjadi langkah strategis dalam menyiapkan santri dengan kompetensi keagamaan yang kuat serta wawasan kekinian yang lebih luas.